INNOVATIVE APPROACHES TO THE FORMATION OF COMMUNICATIONS AT ENTERPRISES IN THE DIGITAL BUSINESS ENVIRONMENT - MIAHKYKH, Irina; DEMYANENKO, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The current stage of economic development is characterized by the rapid digitalization of business processes, global competition and high dynamics of market changes. The digital business environment requires companies not only to implement the latest information and communication technologies, but also to search for innovative solutions in the field of communications with consumers, partners and internal stakeholders. The effectiveness of such solutions depends on the ability of enterprises to quickly adapt to changes and implement modern digital platforms, data analytics, automation of marketing processes and customer relationship management systems, which are becoming key factors in increasing the competitiveness and long-term value of the business.The constant development of digital technologies necessitates the rethinking of traditional communication strategies of enterprises. To ensure business competitiveness, it is important to introduce innovative approaches to the formation of effective channels of interaction with consumers and partners.The main goal of the study is to substantiate and develop innovative approaches to the formation of effective communications at enterprises in the digital business environment, which involves the identification of key principles, tools and technologies of digital interaction, as well as the development of practical recommendations for their implementation to increase competitiveness and sustainable business development.In the conditions of the modern digital age of transformation, communication in the business environment is undergoing significant changes. The growing role of information technology, remote work, globalization of markets and high expectations from customers and partners creates new challenges and requires the introduction of innovative approaches to building effective communication. Traditional methods of interaction between gradually established communication links between employees, customers and other participants in the business environment are giving way to digital solutions that provide speed, flexibility and transparency of information flows.Innovative approaches to the formation of communication in the digital business environment are a powerful driver of change in modern organizations. These technologies open up wide prospects for improving internal and external communication, facilitating more effective interaction between employees, managers, business partners and consumers. The use of tools, including cloud services, artificial intelligence, and augmented reality, significantly expands business opportunities in this direction. The key benefits of these innovations are not only the optimization of teamwork and the improvement of customer service performance, but also the creation of more flexible, scalable and transparent communication processes.
Keywords: innovative approaches; digital business environment; communication processes; digitalization; competitiveness; strategic management